Students’ Interest and Critical Thinking: The Experimental Teaching Method in Using Online Learning Media YouTube - Jamil, Anis Farida; Baiduri, Baiduri; Pratiwi, Amelia Eka (Universitas Pendidikan Ganesha, 2022)
In carrying out learning, educators must be creative in accordance with the demands of technology in developing learning media. YouTube is one of the domains used by educators as an online learning medium. This study aims to determine the effect of using YouTube as an online learning media on students' interest in learning mathematics and critical thinking. The subjects in this study were 20 junior high school students. This study uses the Experimental Teaching method with a quantitative approach. The instruments used are questionnaires and test questions that are given online. Questionnaires were distributed on the subject using a google form and test questions were given after learning using YouTube media. Questionnaires were used to obtain data on interest in learning mathematics and test questions to measure students' critical thinking. Data analysis used paired sample test with a significant level of 0.05. Before carrying out the paired sample test, the normality and homogeneity of the data were tested. The results obtained data are normally distributed and homogeneous. The results showed that there was an effect of using YouTube online learning media on students' interest in learning and critical thinking skills. This is indicated by the significance value for learning interest of 0.017 which is less than 0.05 and the significance value of critical thinking 0.005 which is smaller than 0.05. Furthermore, the value of N-Gain is sought to determine the extent of the influence of YouTube media on interest in learning and critical thinking. The N-Gain value for students' interest in learning mathematics is 0.12 and critical thinking is 0.28. Both values are in the low category so that the influence of YouTube media on interest in learning and critical thinking is less effective.